The Concept of Restorative Justice in the Criminal Legal System: A Breakthrough in Legal Benefits - Walim, Walim (UNISSULA, 2024)
Historically, alternative efforts to resolve criminal cases have existed since the Dutch colonial era, even before Indonesia's independence. Currently, there are several forms of resolving criminal cases outside of court in force, namely diversion (transferring the resolution of children's cases from the criminal justice process to a process outside criminal justice in accordance with the Juvenile Criminal Justice System Law), Afkoop (as regulated in Article 82 of the Criminal Code), and Seponeren (dismissal of cases in the public interest by the Attorney General). The aim of this research is to analyze the concept of restorative justice in the criminal law system as a breakthrough in legal benefits. Approach The research method that can be used in this research is the empirical juridical approach. This approach combines a normative juridical approach with an empirical approach. Based on the analysis carried out, restorative justice can be applied in cases that cause financial loss or minor crimes. The principle of restorative justice in resolving criminal cases in Indonesia does not only depend on formal and material criminal law provisions but is also based on a broader concept of punishment. The model for implementing restorative justice in Indonesian criminal procedural law can be found through a criminal resolution mechanism that follows a legitimate legal problem resolution approach, which is reflected in the reform of the criminal justice system in Indonesia, which is based on an evaluation of the criminal justice system.